PENINGKATAN KETERAMPILAN BERBICARA MELALUI KEGIATAN DISKUSI KELOMPOK DENGAN TEKNIK PROBING PROMPTING PADA SISWA KELAS X SMA NEGERI 3 MAKASSAR - Tumpu, Abu Bakar (AIJER, 2019)
Abstract: Improving Speaking Skill through Group Discussion Activity with Probing Prompting Technique in Class X Students of SMA Negeri 3 Makassar. The main problem in this research was how to apply probing prompting technique through group discussion activities during the learning process. This study aims to improve speaking skills through group discussion activity with probing prompting technique for class X.2 SMA Negeri 3 Makassar. This type of research was a class action research which consisted of 2 cycles where each cycle was held twice. Research procedures included planning, implementation, observation and reflection. The sample in this research was students of class X.2 SMA Negeri 3 Makassar, it consisted of 33 students. The data collection technique in this study was: tests, observation sheets and documentation. The results showed that there was an increase in speaking skil through group discussion activity with probing prompting technique for class X.2 students SMA Negeri 3 Makassar, the provision of cycle I test obtained an average score of 72.06 with a percentage of 73% and increased in the cycle II test obtained 79, 93 with a percentage of 80.0%. Learning Indonesian language by using probing prompting learning technique could improve students' speaking skills.Keywords: Group discussion, probing prompting technique, speaking skill